The peculiarities of structural state of mitochondrial membranes isolated from Antarctic fishes' hepatocytes - V.M. Voitsisky; S. V. Khyzhnyak; L. I. Stepanova; L. V. Sorokina; V. M. Trokhymets (Ukrainian Antarctic Journal, 2010)
The lipid contents, structural and dynamical state of inner mitochondrial membrane from hepatocytes of fishes Notothenia coriiceps, Parachaenichtys charcoti, Chaenocephalus aceratus and Trematomus newnesi taken during the work of the 13th Antarctic expedition were investigated. The differences in structural state of mitochondrial membrane from hepatocytes – the modifications in membrane superficial layer, in the structural order of lipid component, in conformational state of membrane protein molecules, in the content of cholesterol and phospholipids were observed. These modifications could cause the peculiarities of membrane functional activity. It was shown that the more expressed differences are characteristic for Trematomus newnesi. The detected features of structural state of mitochondrial membrane from hepatocytes of Antarctic fishes point out the possibility of existence of different mechanisms that facilitate the metabolic adaptation, particularly the adaptation of energetic processes in hepatocytes of Antarctic fishes at the influence of environmental low temperatures.